2008
DOI: 10.1111/j.1365-2958.2008.06382.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of thiol‐containing proteins in response to quinones in Bacillus subtilis

Abstract: SummaryQuinones are highly toxic naturally occurring thiolreactive compounds. We have previously described novel pathways for quinone detoxification in the Gram-positive bacterium Bacillus subtilis. In this study, we have investigated the extent of irreversible and reversible thiol modifications caused in vivo by electrophilic quinones. Exposure to toxic benzoquinone (BQ) concentrations leads to depletion of numerous Cys-rich cytoplasmic proteins in the proteome of B. subtilis. Mass spectrometry and immunoblot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 58 publications
2
84
0
Order By: Relevance
“…As electrophiles, quinones can form S adducts with cellular thiols via the thiol-(S)-alkylation chemistry. Recently, we showed that toxic quinones react mainly via S-alkylation with cellular thiol-containing proteins in vivo, which leads to aggregation and depletion of proteins in the proteome (18). However, we also found the glyceraldehyde-3-phosphate dehydrogenase GapA as a target for reversible thiol oxidation by quinones in vivo.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…As electrophiles, quinones can form S adducts with cellular thiols via the thiol-(S)-alkylation chemistry. Recently, we showed that toxic quinones react mainly via S-alkylation with cellular thiol-containing proteins in vivo, which leads to aggregation and depletion of proteins in the proteome (18). However, we also found the glyceraldehyde-3-phosphate dehydrogenase GapA as a target for reversible thiol oxidation by quinones in vivo.…”
mentioning
confidence: 75%
“…The polyclonal antisera were used for immunoprecipitation experiments, and the purified antibodies were used at a dilution of 1:200 in the Western blot experiments. Protein amounts of 25 g were loaded onto a 14% SDS-PAGE gel, and the Western blot analysis was performed as described previously (18).…”
Section: Bacterialmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of intracellular metabolites by gas chromatography-mass spectrometry (GC-MS) were performed as described by Liebeke et al (46). Briefly, samples were harvested by fast filtration, and subsequently the metabolism was quenched with an ethanol solution and liquid nitrogen.…”
Section: Analyses Of Intracellular Metabolites By Gc-ms and Lc-msmentioning
confidence: 99%
“…RES include different chemical compounds such as aldehydes, quinones, and the azo compound diamide (2,43,45,46,53,66). Quinones and aldehydes have electron-deficient centers that result in thiol-(S) alkylation of cysteine.…”
mentioning
confidence: 99%